High-Density Lipoproteins Decrease Proinflammatory Activity and Modulate the Innate Immune Response. (2023)
Atherosclerosis, a chronic inflammatory disease of the arterial wall, is the leading cause of cardiac disorders and stroke. The onset and progression of these diseases are linked with the inflammatory response, especially NLRP3 inflammasome activation, inducing the production of proinflammatory cytokines, such as interleukin 1 (IL-1). Because high-density lipoproteins (HDLs) have shown significant antiatherogenic and anti-inflammatory properties, we evaluated their immunomodulatory activity in response to cholesterol crystals and other innate immune activators. Human primary monocyte-derived macrophages, THP-1 cells, and murine macrophages were stimulated to activate NLRP3 inflammasome and other pattern recognition receptors, in the presence or absence of HDL. Then, HDL immunomodulatory effects were evaluated through IL-1 and IL-6 production by enzyme-linked immunosorbent assay. Furthermore, in vivo HDL anti-inflammatory effects were evaluated in a murine model of peritoneal inflammatory infiltration. HDLs have an immunomodulatory effect on different cellular models, including peripheral blood mononuclear cells, THP-1 cells, and murine macrophages, by affecting the activity of innate immunity sensors, such as Toll-like receptors (TLRs), dectin-1, and inflammasomes. HDL reduces the proinflammatory role of cholesterol crystals, nigericin, and other NLRP3 and AIM2 inflammasome agonists, and several TLR agonists, leading to a decreased production of IL-1 and IL-6. The results suggest that HDLs are highly important in the regulation of the innate immune response and may have a beneficial role in controlling diseases associated with the inflammatory response.